112th National Western Mining Conference attracts heavyweights (Society for Mining, Metallurgy & Exploration, 2010)
The 112th Annual National Western Mining Conference (NWMC) hosted by the Colorado Mining Association (CMA) drew some political heavyweights, if by voice only, into the fray of two of the hottest topics that the mining industry is currently facing ? climate change and the new energy economy. A changing political landscape in Colorado, as well as in Washington D.C., has given rise to questions about the economic future of the United States and the mining industry?s role in that future. While there has been a recent push away from traditional energy sources to a ?new energy economy? that is rich in renewable energy sources such as wind and solar, the NWMC?s agenda emphasized the role that minerals will play in new energy technologies. The conference was also full of talks about the industry?s role in reducing the United States? reliance on foreign oil and other mineral commodities. To that end, an impressive lineup of speakers were invited to attend the three-day conference Feb. 8-11, in Denver, CO. Unfortunately, Mother Nature had other plans and three of the four headliners, including Denver?s mayor and Democratic candidate for governor of Colorado, John Hickenlooper, were unable to get to the conference because of a massive blizzard on the East Coast locked them in Washington, D.C. However, with modern technology, a full auditorium heard presentations from Hickenlooper, National Mining Association (NMA) president and chief executive officer Hal Quinn and Glenn Kelly, vice president, government affairs for NMA. Republican candidate for governor of Colorado, Scott McInnis, did speak to the crowd in person.